2022
DOI: 10.3390/buildings12060710
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Building Electricity Consumption on Residents’ Subjective Well-Being: Evidence from China

Abstract: Residential electricity consumption has an important impact on China’s construction of a low-carbon society. However, at present, little of the literature analyzes the influencing factors of residents’ overall well-being from the perspective of micro investigation. Based on the micro mixed cross section data of the Chinese General Social Survey (CGSS), this paper empirically studies the impact of residential electricity consumption on residents’ subjective well-being. In addition, in the heterogeneity analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…The degree of air pollution decreases, and residents’ personal satisfaction significantly improves [ 29 ]. At the same time, residential electricity consumption can improve subjective well-being, narrow the difference between men and women, and improve the problem of educational imbalances [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…The degree of air pollution decreases, and residents’ personal satisfaction significantly improves [ 29 ]. At the same time, residential electricity consumption can improve subjective well-being, narrow the difference between men and women, and improve the problem of educational imbalances [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…(3) Similar research on residential buildings in China revealed that inadequate energy supply has led to low life satisfaction in people living in residential buildings irrespective of their age class. (4) As a way of overcoming this energy problem, most of the affected people have resorted to using non-renewable sources of energy such as diesel and kerosene to sustain their homes. (5) The wide use of non-renewable energy is due to its low cost and easy accessibility.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, favorable social relationships, occupational participation, social and cultural orientations, and engagement enhance residents' happiness [19] . In terms of consumption, increasing residents' electricity consumption can increase their happiness [20] . However, these studies have focused more on developed countries, and few have focused on the impact of Internet use on well-being in developing countries.…”
Section: Introductionmentioning
confidence: 99%